Synthetic biology enables mushrooms to meet emerging sustainable challenges - Zou, Gen; Li, Tian; Mijakovic, Ivan; Wei, Yongjun (Frontiers in Microbiology, 2024)
With the increasing sustainability challenges, synthetic biology is offering new possibilities for addressing the emerging problems through the cultivation and fermentation of mushrooms. In this perspective, we aim to provide an overview on the research and applications mushroom synthetic biology, emphasizing the need for increased attention and inclusion of this rapidly advancing field in future mushroom technology over China and other countries. By leveraging synthetic biology, mushrooms are expected to play a more versatile role in various area, including traditional fields like circular economy, human wellness and pharmaceutics, as well as emerging fields like vegan meat, mushroom-based materials and pollution abatement. We are confident that these efforts using synthetic biology strategies have the potential to strengthen our capacity to effectively address sustainability challenges, leading to the development of a more sustainable social economy and ecology.